KEBIJAKAN DINAS SOSIAL DALAM PENANGANAN ANAK JALANAN DI KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This research raises the subject matter of "How is the Social Service Policy in handling Street Children in Makassar City?" with sub-problems, namely: What is the Social Service Policy in handling Street Children in Makassar City?” And the supporting factors and obstacles experienced by the Social Service in handling street children in Makassar City? This study uses a qualitative research type located at the Makassar City Social Service Office. The research approach used is a social work approach. The primary data sources for this research are Makassar City Social Service employees (key informants), additional informants are street children and parents of street children. Secondary data sources are books, research results, and other documents related to this research that are complementary to primary data. The methods of collection are observation, in-depth interviews, and documentation. Data analysis with three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Makassar City Social Service issued a policy in the form of patrols and carried out a training policy for 7 days. The supporting factors obtained by the Social Service in terms of handling street children in Makassar City are the political will from the Makassar City government as a city free from street children. Second, there is good cooperation between the Makassar Social Service patrol team and the Satpol PP and Police. The inhibiting factors are the increasing number of street children every year and the absence of a special place that can be used as a place for fostering street children who are successful in raids. The implication of this research is that one of the policies of the Social Service regarding the handling of street children is that outreach must be developed and improved both in terms of further guidance and practice. The Makassar City Government should immediately build a special orphanage for street children which be directly fostered by social workers to improve and optimize policies for handling street children so as to reduce the number of street children each year.